The expanding nutraceutical market: a critical review - Batta, Angelika; Singh, Sunita; Prasad, Anisha (International Journal of Basic & Clinical Pharmacology, 2026)
The global nutraceutical industry is expanding rapidly, driven by growing emphasis on preventive healthcare, lifestyle modification, and consumer preference for natural therapeutic options. Derived from the convergence of “nutrition” and “pharmaceutical,” nutraceuticals bridge food and medicine, offering potential benefits in health promotion and disease prevention; however, concerns regarding their safety, efficacy, standardization, and regulatory oversight persist. Traditional systems such as Ayurveda and Traditional Chinese Medicine provide conceptual foundations for many modern nutraceutical formulations. This narrative review examines key distinctions between nutraceuticals and pharmaceuticals, evaluates the benefits and limitations of synthetic and herbal nutraceuticals, and analyzes regulatory frameworks across India, the United States, and Europe. Findings indicate that while nutraceuticals offer accessibility, affordability, and preventive health advantages, they face challenges related to product variability, adulteration, and unsubstantiated health claims. Regulatory mechanisms remain inconsistent globally, with oversight by FSSAI in India, the FDA under DSHEA in the U.S., and EFSA in Europe. Current market trends highlight growing demand for personalized, plant-based, and clean-label products, with the Indian nutraceutical sector projected to grow at a CAGR of nearly 10% through 2030. Sustainable advancement of the industry requires robust scientific validation, harmonized regulation, and ethical marketing to ensure efficacy, safety, and consumer trust.